HAMBATAN-HAMBATAN YANG DIHADAPI CINA DALAM MELINDUNGI ALIRAN MINYAK BUMI DARI ANCAMAN INDIA - Randy Julio Putra (Universitas Jenderal Ahmad Yani, 2019)
The increasing usage of electricity and transportation also the rapid industrial growth are three factors that cause China’s demand on crude oil supply keep increasing. Because of its limited capacity to produce its own oil, China leave with no choice but to become an oil importing country. Middle East is China’s biggest oil supplier. The high dependency on Middle East oil supply make China become highly dependent on Malacca Strait. India naval facility in Andaman and Nicobar Islands and its partnership with The United States perceived as a threat to the oil supply that flow through the Malacca Strait. This paper aim is to explore obstacles that China face in protecting its own oil supply from India.